Iron-based nanocrystalline soft magnetic alloy and preparation method thereof

Through the method of assisting stress elimination annealing and crystallization treatment with magnetic field, the challenges of existing iron-based/α-Fe nanocomposite thin strips in improving saturated magnetic induction strength and reducing coercive force are solved, and the comprehensive magnetic performance of high saturated magnetic induction strength and low coercive force is achieved.

CN119663122APending Publication Date: 2025-03-21JIANGYIN KANGRUI MOLDING TECH CO LTD

Patent Information

Application Number
CN202311208770.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing iron-based/α-Fe nanocomposite thin strips have challenges in improving saturated magnetic induction strength and reducing coercive force, and high Fe content leads to a decrease in the content of non-magnetic amorphous elements, affecting mechanical and magnetic properties.

Method used

The magnetic field assists stress elimination and annealing and then crystallization is used to induce only a very small amount of nanocrystals precipitation, and combines the traditional smelting and single-roll belt-swinging method to prepare the tape.

Benefits of technology

With low coercive force, higher saturated magnetic induction strength can be obtained and good bending toughness can be maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663122A_ABST
    Figure CN119663122A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based nanocrystalline soft magnetic alloy and a preparation method thereof. A magnetically soft alloy strip is prepared through smelting and a single-roller melt-spinning method, stress relief annealing is carried out on the magnetically soft alloy strip through assistance of a magnetic field, and then crystallization annealing treatment is carried out. Different from a traditional method for regulating and controlling the magnetic performance of the alloy through precipitation of a large number of nanocrystals, the method only induces precipitation of a very small number of nanocrystals, and high saturation flux density and low coercive force can be obtained while the toughness of the strip is ensured; the iron-based nanocrystalline soft magnetic alloy with high saturation flux density and low coercive force can be prepared by taking Fe as a main element, Co element with the atomic fraction lower than 8%, Cu element with the atomic fraction lower than 1% and at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and the like as other trace elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to an iron-based nanocrystalline soft magnetic alloy and a preparation method thereof. Background Art

[0002] Iron-based nanocrystalline soft magnetic alloys, also known as iron-based / α-Fe amorphous nanocrystalline soft magnetic alloys, or iron-based / α-Fe nanocomposite thin ribbons, are expected to be promoted and applied in new energy, 5G communications, power electronics and other fields due to their superior properties such as high saturation magnetic induction intensity, low-loss soft magnetic properties and high effective magnetic permeability, in order to meet the needs of modern electronic and electrical equipment to develop in the direction of high frequency, high efficiency, lightweight and energy saving. However, although amorphous strips can obtain higher saturation magnetic induction (1.67-1.8T), they are still not comparable to traditional silicon steel. Increasing the Fe content is an effective way to increase the saturation magnetic induction of the strip. To this end, researchers have carried out a series of studies such as Fe 83.3-84.3 Si4B8P 3-4 Cu 0.7 , Fe 85 B 13 Ni2、Fe 83.2 P8B2C6Cu 0.8 In fact, the increase of Fe content will inevitably lead to a decrease in the content of non-magnetic amorphous glass-forming elements, which in turn affects the amorphous glass-forming ability and overall mechanical and magnetic properties of the strip. Therefore, it is imperative to explore new ways to improve the comprehensive magnetic and mechanical properties of the strip by regulating the alloy composition and optimizing the preparation process.

[0003] At present, researchers have conducted a series of related studies and applied for a number of national invention patents for the optimization design of the comprehensive magnetic properties of Fe-based / α-Fe nanocomposite ribbons, including:

[0004] In patent CN109112434A, Guangdong University of Technology announced a new type of iron-based amorphous nanocrystalline soft magnetic alloy and its preparation method, pointing out that heating the strip to 410-450℃ at a heating rate of 10-20℃ / min and then cooling to room temperature can obtain a higher saturation magnetic induction intensity and low coercive force, and the alloy exhibits good bending toughness, but the complex alloy system containing precious metal elements is not conducive to the commercial production of the strip.

[0005] The Ningbo Institute of Materials Technology and Engineering of the Chinese Academy of Sciences published a kind of iron-based nanocrystalline soft magnetic alloy and its preparation method in patent CN105448448A. The chemical composition of the alloy includes Fe, Cu, P and C, and the specific content (atomic percentage) is: Fe = 83.25%, Cu = 0.75%, P = 10%, C = 6%. The production process adopts vacuum melting of the master alloy, and then single-roller rapid cooling and spraying of the amorphous strip in Ar atmosphere. However, the annealing process needs to be carried out in a rapid heating furnace, and the saturation magnetic induction intensity of the obtained alloy strip is relatively low, with a maximum of 1.69T.

[0006] Shenzhen Dongda Innovation Technology Co., Ltd. published a nanocrystalline soft magnetic material and its preparation method in patent CN1392573A. The chemical composition of the alloy includes Fe, Ni, P, B, Cu and Nb, and the specific content (atomic percentage) is: Fe = 60-64%; Ni = 12-18%; P = 13-16%; B = 5-7%; Cu = 0-2%; Nb = 0-3%. The production process adopts ball milling, ball milling at different speeds for 30-80 hours, and then heated to any temperature between the crystallization temperature and 30°C above the crystallization temperature in an inert gas atmosphere and kept warm for 0.5-1 hour. The saturation magnetic induction intensity of the obtained alloy is not high, the iron loss is high, and the processing is also relatively complicated.

[0007] Although the above research work has improved the soft magnetic properties of iron-based / α-Fe nanocomposite thin strips to varying degrees, the heat treatment process has stringent requirements on the process, and the prepared target alloy cannot achieve high saturation magnetic induction intensity and low coercivity at the same time. In addition, the alloy composition contains precious metal elements, which leads to a high cost of the alloy, and contains volatile elements such as P, which makes the processing technology difficult to accurately control. Therefore, exploring new methods to improve the comprehensive magnetic properties of the strip is of great significance for the current research and application of iron-based soft magnetic alloy materials. Summary of the invention

[0008] In view of the above problems, the present invention proposes an iron-based nanocrystalline soft magnetic alloy and a preparation method, which uses a magnetic field to assist in stress relief annealing of the strip and then performs a crystallization treatment. This method only induces very little nanocrystal precipitation, which ensures the toughness of the strip while obtaining high saturation magnetic induction intensity and low coercive force.

[0009] The present invention discloses a method for preparing an iron-based nanocrystalline soft magnetic alloy, wherein the iron-based nanocrystalline soft magnetic alloy is also called an iron-based soft magnetic alloy or an iron-based nanocomposite thin strip, and adopts a smelting and heat treatment process, and is characterized in that it comprises the following steps:

[0010] S1: raw material smelting, placing the soft magnetic alloy smelting raw materials into an induction melting furnace according to the atomic and molecular ratio and fully melting them;

[0011] S2: preparing the strip by a single-roll strip-spinning method, wherein the soft magnetic alloy melt (including part of the master alloy ingot melted again by an induction melting furnace after the melting in step S1) is quickly sprayed onto the surface of a single roller rotating at a high speed to prepare an iron-based amorphous quenched strip;

[0012] S3: Magnetic field assisted stress relief annealing, cutting the quenched strip into alloy strips of a specified length (generally the specified length is between 50 and 70 mm) and then loading them into a quartz tube matched with a magnetic field annealing furnace, and performing stress relief annealing with the assistance of a longitudinal magnetic field;

[0013] S4: Crystallization annealing, which is performed at high temperature. The alloy strip is placed in a heat treatment furnace and vacuumed to less than 3×10 -3 Pa, and then quickly quenched to room temperature after annealing to obtain an iron-based nanocrystalline soft magnetic alloy.

[0014] Furthermore, after the strip is loaded into a quartz tube matched with the magnetic field annealing furnace, the magnetic field is applied while the quartz tube containing the sample is pushed into the annealing furnace cavity, and the magnetic field strength is 1000-1700 Oe (Oersted, a unit of magnetic field strength).

[0015] Furthermore, the stress relief annealing temperature is selected between 150 and 300° C. and is below the Curie temperature and the initial crystallization temperature. The stress relief annealing time is 2 to 10 minutes.

[0016] Furthermore, the temperature during the crystallization annealing (heat treatment) is selected between the initial temperature corresponding to the first crystallization peak and the initial crystallization temperature of the second crystallization peak; the crystallization annealing is carried out in a rapid heating annealing furnace with a heating rate of 20 to 28°C / s. After the annealing is completed, it is quickly quenched to room temperature in order to effectively slow down the nucleation and growth of nanocrystals. The crystallization annealing time is 2 to 3 minutes.

[0017] Furthermore, the magnetic field assisted stress relief annealing temperature is selected at 150°C, which is lower than both the Curie temperature and the initial crystallization temperature; the magnetic field assisted stress relief annealing time is 10 minutes; the stress relief annealing magnetic field strength is 1000Oe; the crystallization annealing heating rate is 20°C / s, and the temperature is 390°C, which is near the initial temperature corresponding to the first crystallization peak; the crystallization annealing (heat treatment) time is 2 minutes.

[0018] Furthermore, the magnetic field assisted stress relief annealing temperature is selected at 250°C, the annealing time is 5 minutes, and the magnetic field strength is 1500Oe; the crystallization annealing heating rate is 25°C / s, the temperature is 410°C, and the crystallization annealing time is 3 minutes.

[0019] Furthermore, the magnetic field assisted stress relief annealing temperature is selected at 280°C, the annealing time is 5 minutes, and the magnetic field strength is 1500Oe; the crystallization annealing heating rate is 28°C / s, the temperature is 450°C, and the crystallization annealing time is 3 minutes.

[0020] Furthermore, the magnetic field assisted stress relief annealing temperature is selected at 280°C, the annealing time is 4 minutes, and the magnetic field strength is 1500Oe; the crystallization annealing heating rate is 28°C / s, the temperature is 450°C, and the crystallization annealing time is 2 minutes.

[0021] Furthermore, the magnetic field assisted stress relief annealing temperature is selected at 300°C, the annealing time is 2 minutes, and the magnetic field strength is 1700Oe; the crystallization annealing heating rate is 28°C / s, the temperature is 430°C, and the crystallization annealing time is 2 minutes.

[0022] On the other hand, an iron-based nanocrystalline soft magnetic alloy is provided, characterized in that the alloy is prepared according to any one of the above-mentioned methods for preparing an iron-based nanocrystalline soft magnetic alloy.

[0023] Furthermore, the soft magnetic alloy contains Co element with an atomic fraction ratio (molar fraction) not higher than 8% and Cu element with an atomic fraction ratio not higher than 1%, and the remaining trace elements are at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and the like; the purity of the raw materials is greater than 99%.

[0024] Furthermore, the soft magnetic alloy molecular formula composition satisfies: Fe 77.2 6B 10 C6 0.8 .

[0025] Furthermore, the soft magnetic alloy material has good bending toughness and does not break after being bent 180 degrees. At the same time, the alloy has excellent comprehensive magnetic properties, and its saturation magnetic induction intensity is 1.78-1.85T.

[0026] The advantages and beneficial effects of the present invention are as follows: the method for preparing the iron-based nanocrystalline soft magnetic alloy proposed in the present invention has a relatively simple process. In addition to the traditional smelting and single-roller strip spinning preparation process, stress relief annealing assisted by a magnetic field is applied before crystallization annealing, which can effectively hinder the nucleation and growth of nanocrystals. By controlling the appropriate temperature, time, and magnetic field strength, a higher saturation magnetic induction intensity can be obtained while ensuring low coercivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The invention relates to the steps of a method for preparing an iron-based nanocrystalline soft magnetic alloy;

[0028] Figure 2It is the XRD (x-ray diffraction) spectrum of amorphous strip prepared by smelting;

[0029] Figure 3 is the DSC-TG (differential scanning calorimetry-thermogravimetric analysis) curve of the amorphous ribbon;

[0030] Figure 4 It is a diagram of the changes in microstructure under different heat treatment processes. DETAILED DESCRIPTION

[0031] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0032] Example 1

[0033] like Figure 1 As shown, the present invention is designed to prepare an iron-based nanocrystalline soft magnetic alloy, the iron-based nanocrystalline soft magnetic alloy is also called an iron-based soft magnetic alloy, or an iron-based nanocomposite thin strip, using a smelting and heat treatment process, characterized in that it includes the following steps:

[0034] S1: Raw material smelting: the raw materials for soft magnetic alloy smelting are placed in an induction melting furnace according to the ratio of atomic number and molecular number, and fully melted; this embodiment adopts a WK-Ⅱ vacuum arc melting furnace (manufactured by Beijing Wuke Co., Ltd.), and the molecular formula meets the requirements of Fe 77.2 6B 10 C6 0.8 The raw materials are smelted according to the composition ratio, and the purity of each raw material is greater than 99%;

[0035] S2: preparing a strip by a single-roll strip-spinning method, wherein the molten soft magnetic alloy (including part of the master alloy ingot melted in step S1 and melted again in an induction melting furnace) is used to prepare an iron-based amorphous quenched strip by a single-roll strip-spinning method;

[0036] S3: Magnetic field assisted stress relief annealing, the quenched strip is cut into alloy strips of a specified length (generally the specified length is between 50 and 70 mm, and the specified length in this embodiment is 60 mm), and then loaded into a quartz tube matched with a magnetic field annealing furnace (this embodiment adopts a CCRCL-16-I type vacuum transverse magnetic / longitudinal magnetic heat treatment furnace), and stress relief annealing is performed with the assistance of a magnetic field, and a longitudinal magnetic field is applied in this embodiment;

[0037] S4: Crystallization annealing. The crystallization annealing is performed at a high temperature. The alloy strip is placed in a heat treatment furnace (RTP-S90B single-end slide rail furnace is used in this embodiment) and vacuumed to less than 3×10 -3Pa, and then quickly quenched to room temperature after annealing to obtain an iron-based nanocrystalline soft magnetic alloy.

[0038] The first two steps are the material smelting preparation process, which is the conventional step for the preparation of iron-based / α-Fe amorphous nanocrystalline soft magnetic alloys. The last two steps are the heat treatment process, and the process and parameter combination have a greater impact on the performance.

[0039] Preferably, after the strip is loaded into a quartz tube matched with the magnetic field annealing furnace, the magnetic field is applied while the quartz tube containing the sample is pushed into the annealing furnace cavity, and the magnetic field strength is 1000-1700 Oe (Oersted, a unit of magnetic field strength).

[0040] Preferably, the stress relief annealing temperature is selected between 150 and 300° C. and is below the Curie temperature and the initial crystallization temperature. The stress relief annealing time is 2 to 10 minutes. Figure 1 The Curie temperature of this embodiment is shown to be 453°C and the initial crystallization temperature is 390°C.

[0041] Preferably, the temperature during the crystallization annealing (heat treatment) is selected between the initial temperature corresponding to the first crystallization peak and the initial crystallization temperature of the second crystallization peak, such as Figure 1 T x1 and T x2 In this embodiment, the temperature is selected to be between 390 and 490°C; the crystallization annealing is carried out in a rapid heating annealing furnace with a heating rate of 20 to 28°C / s. After the annealing, it is quickly quenched to room temperature in order to effectively slow down the nucleation and growth of nanocrystals. The crystallization annealing time is 2 to 3 minutes; if the crystallization annealing time is too short, the nucleation of nanocrystals will not be utilized, while if the time is too long, the nucleation and rapid growth of nanocrystals will be caused, which will greatly deteriorate the soft magnetic properties of the alloy. Therefore, based on a large number of experiments, the present invention preferably uses a 2-3 minute heat treatment.

[0042] Preferably, the magnetic field assisted stress relief annealing temperature of this embodiment is selected at 150°C, which is lower than the Curie temperature and the initial crystallization temperature at the same time; the magnetic field assisted stress relief annealing time is 10 minutes; the stress relief annealing magnetic field strength is 1000Oe; the crystallization annealing heating rate is 20°C / s, and the temperature is 390°C, which is near the initial crystallization temperature of the first crystallization peak; the crystallization annealing (heat treatment) time is 2 minutes, and the saturation magnetic induction intensity Bs of the soft magnetic alloy material is 1.79T, and the coercive force is 24.9A / m.

[0043] Example 2

[0044] The difference from Example 1 is that the magnetic field-assisted stress relief annealing temperature in this embodiment is selected at 250°C, the annealing time is 5 minutes, and the magnetic field strength is 1500Oe; the crystallization annealing heating rate is 25°C / s, the temperature is 410°C, and the crystallization annealing time is 3 minutes, and the saturation magnetic induction intensity Bs of the soft magnetic alloy material is 1.80T and the coercive force is 13.2A / m.

[0045] Example 3

[0046] The difference from Example 1 is that the magnetic field-assisted stress relief annealing temperature in this embodiment is selected at 280°C, the annealing time is 5 minutes, and the magnetic field strength is 1500Oe; the crystallization annealing heating rate is 28°C / s, the temperature is 450°C, and the crystallization annealing time is 3 minutes, and the saturation magnetic induction intensity Bs of the soft magnetic alloy material is 1.85T and the coercive force is 201.7A / m.

[0047] Example 4

[0048] The difference from Example 1 is that the magnetic field-assisted stress relief annealing temperature in this embodiment is selected at 280°C, the annealing time is 4 minutes, and the magnetic field strength is 1500Oe; the crystallization annealing heating rate is 28°C / s, the temperature is 450°C, and the crystallization annealing time is 2 minutes, and the saturation magnetic induction intensity Bs of the soft magnetic alloy material is 1.82T and the coercive force is 8.54A / m.

[0049] Example 5

[0050] The difference from Example 1 is that the magnetic field-assisted stress relief annealing temperature in this embodiment is selected at 300°C, the annealing time is 2 minutes, and the magnetic field strength is 1700Oe; the crystallization annealing heating rate is 28°C / s, the temperature is 430°C, and the crystallization annealing time is 2 minutes, and the saturation magnetic induction intensity Bs of the soft magnetic alloy material is 1.80T and the coercive force is 9.49A / m.

[0051] Example 6

[0052] An iron-based nanocrystalline soft magnetic alloy is prepared according to the method for preparing an iron-based nanocrystalline soft magnetic alloy described in any one of the above embodiments, i.e., new parameter combinations that meet the combination conditions.

[0053] Preferably, the soft magnetic alloy contains Co element with an atomic fraction ratio (molar fraction) not higher than 8% and Cu element with an atomic fraction ratio not higher than 1%, and the remaining trace elements are at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and the like; the purity of the raw materials is greater than 99%.

[0054] Preferably, the soft magnetic alloy molecular formula composition satisfies: Fe 77.2 6B 10C6 0.8 .

[0055] The soft magnetic alloy material obtained in the experiment of this embodiment has good bending toughness and does not break after being bent at 180 degrees. At the same time, the alloy has excellent comprehensive magnetic properties, and its saturation magnetic induction intensity is 1.78-1.85T.

[0056] Comparative Example

[0057] In order to verify the effectiveness of the present invention, the present invention selects a prior art comparative example for comparative analysis with the present embodiment. The comparative example has a high saturation magnetic induction iron-based amorphous soft magnetic alloy, and its molecular formula composition is: Fe 83.2 B 10 C6 0.8 .

[0058] The alloy structure, thermal properties, and magnetic properties testing methods are exactly the same as those described in the examples.

[0059] Attached Figure 2 The figure shows the XRD (x-ray diffraction) spectrum of the amorphous ribbon obtained by smelting preparation (steps S1 and S2), and the XRD is measured using a D8 Advance polycrystalline X-ray diffractometer. As can be seen from the figure, the XRD spectrum of the embodiment and the comparative example both shows a diffuse scattering peak, and no obvious crystallization diffraction peak appears, which is a typical amorphous structure.

[0060] Attached Figure 3 The DSC-TG (differential scanning calorimetry-thermogravimetric analysis) curve of the amorphous strip prepared by smelting is shown, wherein the DSC curve is measured by a NETZSCH DSC 404C differential scanning calorimeter, and the measured heating rate is 0.67°C / s, and the heating rate of the TG curve test is 0.33°C / s. It can be seen from the DSC curve (a) that compared with the comparative example, the initial crystallization exothermic peak temperature (TX1) of the embodiment is slightly shifted to the left, and the initial crystallization exothermic peak temperature (TX2) of the second exothermic peak is shifted to the right. Therefore, a larger crystallization heat treatment window (△T=TX2-TX1) can be obtained. This △T is the optimal heat treatment temperature range for obtaining the nanocrystalline structure required for excellent soft magnetic alloys. In addition, the Curie temperature (TC) of the comparative example and the embodiment alloy can be clearly seen from the TG curve (b), and it is found that the Curie temperature of the embodiment strip is significantly higher than that of the comparative example strip, indicating that the former has better high-temperature magnetic properties (mainly caused by the material).

[0061] Attached Figure 4The diagrams of the changes in the microstructure of the strips prepared in the embodiments of the present invention and the comparative examples under different heat treatment processes (250°C stress relief annealing for 5 minutes and then annealing at a crystallization temperature of 450°C for 2 minutes). As can be seen from Figures (b), (d), and (f), the alloy of the embodiment that was subjected to stress relief annealing at 250°C for 5 minutes and then annealing at a crystallization temperature of 450°C for 2 minutes has undergone obvious crystallization. When the alloy was annealed at 450°C for 2 minutes after the longitudinal magnetic field was assisted during the stress relief annealing at 250°C, a very small amount of small-sized nanocrystals precipitated from the amorphous matrix. Compared with the microstructure without the assistance of the magnetic field, this structure has less effect on the bending brittle fracture of the strip itself, so the alloy still exhibits good bending toughness. At the same time, the synergistic effect of the nanocrystals and the amorphous matrix causes the alloy to have excellent comprehensive magnetic properties. When the strip was annealed at 450℃ for 3 minutes under the condition of magnetic field assisted stress relief, nanocrystals with a fine and uniform average grain size of 48nm were largely precipitated from the amorphous matrix. Although this organization is beneficial to the saturation magnetic induction intensity of the alloy, the coercivity and the bending performance of the strip were greatly deteriorated. For the comparative example (Figures (a), (c), (e)), only a very small amount of nanocrystals were observed in the alloy after annealing at 250℃ for 5 minutes and then annealing at the crystallization temperature of 450℃ for 2 minutes, while when the alloy was annealed at 450℃ for 2 minutes after the longitudinal magnetic field assisted the stress relief annealing process at 250℃, even fewer nanocrystals could be observed. Under this condition, after the crystallization treatment for 3 minutes, a large amount of nanocrystals with a relatively uniform average grain size of 28nm were precipitated from the amorphous matrix, similar to the embodiment, indicating a serious crystallization phenomenon of the alloy. Therefore, these results all show that the number and size of nanocrystals precipitated from the amorphous matrix of the alloy after the magnetic field assisted stress relief was reduced after appropriate time and temperature treatment. This structure can ensure that the alloy has good bending toughness while having good comprehensive magnetic properties, namely high saturation magnetic induction intensity and low coercive force.

[0062] In order to further illustrate the influence of the process method on the material properties, the following Tables 1 to 3 respectively list the test results of the soft magnetic alloy properties under different process parameters of the comparative examples and the embodiments.

[0063] Table 1: Data on the variation of magnetic properties of the embodiments of the present invention and the comparative examples under conventional annealing methods with temperature and holding time

[0064] (Saturation magnetic flux density Bs (T), coercive force Hc (A / m))

[0065]

[0066] Table 2: Magnetic property change data of the embodiments of the present invention and the comparative examples after stress relief annealing for 5 minutes without magnetic field and keeping at different temperatures for 2 minutes

[0067] (Saturation magnetic flux density Bs (T), coercive force Hc (A / m))

[0068]

[0069] Table 3: Magnetic property change data of the embodiments of the present invention and the comparative examples after 5 minutes of magnetic field assisted stress relief annealing at different temperatures and different holding times

[0070] (Saturation magnetic induction intensity Bs (T), coercive force Hc (A / m), F indicates that there is a magnetic field assisting in the stress relief annealing process)

[0071]

[0072] As can be seen from Table 1, under the traditional annealing method, as the holding temperature increases, the saturation magnetic induction of the comparative example gradually increases, while the coercive force first decreases and then increases; compared with the embodiment (different materials), the coercive force gradually increases while the saturation magnetic induction increases. In particular, after being held at 450°C for three minutes, the saturation magnetic induction of the two samples increases while the coercive force increases sharply, indicating that the structures of the embodiment and the comparative example have undergone significant changes under this condition.

[0073] When the annealing process is changed from traditional annealing to stress relief annealing + crystallization temperature annealing, it can be seen from Table 2 that the saturation magnetic induction of the embodiment still increases with the increase of the holding temperature, on the contrary, the saturation magnetic induction of the comparative example shows fluctuation. The coercive force shows a trend of first decreasing and then increasing, indicating that the change of the annealing process has a greater impact on the comprehensive magnetic properties of the alloy.

[0074] The annealing process of the alloy is further changed, that is, a magnetic field is applied during the stress relief annealing process to regulate the magnetic domain, and then the heat preservation annealing treatment is carried out at different crystallization temperatures. The results are shown in Table 3. It can be clearly seen that the saturation magnetic induction of the embodiment changes similarly to that in Table 2, gradually increasing with increasing temperature, while the saturation magnetic induction of the comparative example shows a trend of first increasing and then decreasing. When the crystallization heat preservation time increases from 2 minutes to 3 minutes, the saturation magnetic induction of the embodiment and the comparative example increases sharply. This is because under this heat preservation time, a large amount of nanocrystals precipitate from the amorphous matrix, and the increase in its crystallized volume fraction leads to an increase in the saturation magnetic induction of the alloy system, which is consistent with the above. Figure 3 The results of (e) and (f) are consistent; however, the coercive force increases significantly with prolonged holding time, and further process optimization research is needed.

[0075] For soft magnetic alloys, it is generally difficult to increase the saturation magnetic induction intensity, but the influence of the material's coercive force can be overcome by a reverse magnetic field, which is generally lower than 10Oe (1Oe≈79.6A / m). Although the material of the present invention sacrifices a little coercive force performance, it obtains an increase in saturation magnetic induction intensity, thereby improving its comprehensive application performance.

[0076] It is worth noting that the coercive force under this annealing method is significantly different from the coercive force change under the annealing methods in Table 1 and Table 2, that is, the coercive force of the embodiment and the comparative example gradually decreases with the increase of the holding temperature, indicating that this annealing method significantly improves the soft magnetic properties of the alloy while increasing the saturation magnetic induction of the system, confirming that the magnetic field assisted stress relief annealing + crystallization temperature annealing of the present invention is an effective and feasible method for regulating the magnetic properties and bending toughness of the strip.

[0077] The above experiments not only show the influence of the process on the material properties, but also show the performance differences of different material compositions.

[0078] The basic principle of the present invention is that applying a magnetic field can effectively hinder the nucleation and growth of nanocrystals, so that the amorphous material still exhibits a good amorphous matrix under a heat treatment process of 250-F-2min (or other combinations), and the precipitation of a small amount of α-Fe nanocrystals and the interaction between the amorphous matrix and the amorphous matrix result in a higher Bs value of the alloy; at the same time, because of the magnetic field, the magnetic domains on the inner surface of the strip are all turned to the direction of the external magnetic field, thereby reducing the magnetic anisotropy of the system. Although the precipitation of a small amount of nanocrystals increases the magnetocrystalline anisotropy of the system, the overall magnetic anisotropy is reduced under the annealing process, so the coercive force of the alloy is relatively low.

[0079] The above are only some embodiments of an iron-based nanocrystalline soft magnetic alloy and a preparation method of the present invention. It can be seen from the embodiments that there are many combinations of process parameter selections for the preparation method, and these combinations should also be regarded as the protection scope of the present invention and will not be listed one by one here.

Claims

1. A method for preparing an iron-based nanocrystalline soft magnetic alloy, using a smelting and heat treatment process, characterized in that: The steps include: S1: raw material smelting, placing the soft magnetic alloy smelting raw materials into a smelting furnace according to the atomic and molecular ratio and fully smelting; S2: single-roller strip spinning method is used to prepare the strip, and the molten soft magnetic alloy is used to prepare the iron-based amorphous quenched strip; S3: Magnetic field assisted stress relief annealing, cutting the quenched strip into alloy strips of a specified length and then loading them into a quartz tube matched with a magnetic field annealing furnace, and performing stress relief annealing with the assistance of a magnetic field; S4: Crystallization annealing, which is performed at high temperature. The alloy strip is placed in a heat treatment furnace and vacuumed to less than 3×10 -3 Pa, and then quickly quenched to room temperature after annealing to obtain an iron-based nanocrystalline soft magnetic alloy.

2. The method for preparing an iron-based nanocrystalline soft magnetic alloy according to claim 1, characterized in that: After the strip is loaded into a quartz tube matched with the magnetic field annealing furnace, the magnetic field is applied while the quartz tube containing the sample is pushed into the furnace chamber of the annealing furnace, and the magnetic field strength is 1000-1700 Oe.

3. An iron-based nanocrystalline soft magnetic alloy and preparation method according to claim 2, characterized in that: The stress relief annealing temperature is selected between 150 and 300° C. and is below the Curie temperature and the initial crystallization temperature. The stress relief annealing time is 2 to 10 minutes.

4. A method for preparing an iron-based nanocrystalline soft magnetic alloy according to any one of claims 1 to 3, characterized in that: The temperature of the crystallization annealing is selected between the initial temperature corresponding to the first crystallization peak and the initial crystallization temperature of the second crystallization peak; the crystallization annealing is performed in a rapid heating annealing furnace with a heating rate of 20 to 28°C / s, and the crystallization annealing time is 2 to 3 minutes.

5. The method for preparing an iron-based nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The magnetic field assisted stress relief annealing temperature is selected at 150° C., the annealing time is 10 minutes, and the annealing magnetic field strength is 1000 Oe; the crystallization annealing heating rate is 20° C. / s, the temperature is 390° C., and the crystallization annealing time is 2 minutes.

6. The method for preparing an iron-based nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The magnetic field assisted stress relief annealing temperature is selected at 250° C., the annealing time is 5 minutes, and the magnetic field strength is 1500 Oe; the crystallization annealing heating rate is 25° C. / s, the temperature is 410° C., and the crystallization annealing time is 3 minutes.

7. The method for preparing an iron-based nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The magnetic field assisted stress relief annealing temperature is selected at 280° C., the annealing time is 5 minutes, and the magnetic field strength is 1500 Oe; the crystallization annealing heating rate is 28° C. / s, the temperature is 450° C., and the crystallization annealing time is 3 minutes.

8. The method for preparing an iron-based nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The magnetic field assisted stress relief annealing temperature is selected at 280° C., the annealing time is 4 minutes, and the magnetic field strength is 1500 Oe; the crystallization annealing heating rate is 28° C. / s, the temperature is 450° C., and the crystallization annealing time is 2 minutes.

9. The method for preparing an iron-based nanocrystalline soft magnetic alloy according to claim 1, characterized in that: The magnetic field assisted stress relief annealing temperature is selected at 300° C., the annealing time is 2 minutes, and the magnetic field strength is 1700 Oe; the crystallization annealing heating rate is 28° C. / s, the temperature is 430° C., and the crystallization annealing time is 2 minutes.

10. An iron-based nanocrystalline soft magnetic alloy, characterized in that: The alloy is prepared according to the method for preparing an iron-based nanocrystalline soft magnetic alloy according to any one of claims 1 to 9.

11. The iron-based nanocrystalline soft magnetic alloy according to claim 10, characterized in that: The soft magnetic alloy contains Co element with an atomic fraction ratio not higher than 8% and Cu element with an atomic fraction ratio not higher than 1%, and the remaining trace elements are at least one of oxygen, sulfur, phosphorus, carbon, silicon, boron and the like; the purity of the raw materials is greater than 99%.

12. The iron-based nanocrystalline soft magnetic alloy according to claim 11, characterized in that: The soft magnetic alloy material molecular formula composition satisfies: Fe 77.2 6B 10 C6 0.8 .

13. The iron-based nanocrystalline soft magnetic alloy according to claim 12, characterized in that: The soft magnetic alloy material does not break after being bent 180 degrees, and its saturation magnetic induction intensity is 1.78-1.85T.

Citation Information

Patent Citations

  • Iron-based nanocrystalline magnetically soft alloy and preparation method thereof

    CN105448448A

  • New-type iron-based amorphous-nanocrystalline magnetically soft alloy and preparation method thereof

    CN109112434A

  • Nano crystal soft magnetic material and its preparing method

    CN1392573A

Cited By

  • Iron-based amorphous magnetically soft alloy strip and preparation method and application thereof

    CN121428439A

  • Iron-based amorphous soft magnetic alloy ribbon, method of making and use thereof

    CN121428439B